Solar Cycle Variability in Coronal Holes and Their Effects on Solar Wind Sources - J. G. Luhmann; Yan Li; C. O. Lee; L. K. Jian; C. N. Arge; P. Riley (Space Weather)
Abstract Various upstream spacecraft have now observed the solar wind conditions affecting the Earth since the 1970s, covering over four solar activity cycles. These measurements provide a long term picture of the related patterns in large scale incident plasma and magnetic field parameters of interest for both interpreting cycles in geospace effects, and understanding how the Sun controls our space environment. This paper focuses on the latter, in part to provide context at the start of the new solar cycle 25, and toward establishing connections between the 1 AU ecliptic solar wind behavior and the unprecedented near‐Sun measurements of heliospheric features on Parker Solar Probe and Solar Orbiter. Magnetograph data‐based potential field source surface models provide a basic picture of how the solar wind sources, including those that give rise to corotating high speed streams in the ecliptic, have changed since the beginning of the record of regular solar wind measurements. In particular, they suggest the contributions from low to mid latitude coronal holes dominate the observed cycles (21–24), especially the weaker cycles (23 and 24), impacting upstream measurement interpretations, modeling, and forecasting considerations. For example, recurring features are affected by differential rotation of the Sun's surface field, which through its effects on the corona, can produce solar wind streams reappearing at ∼25–30 days intervals instead of at the canonical 27.3 days Carrington rotation rate. In addition, the conditions that lead to the corotating stream structure that can dominate periods of low solar activity are seen to be more complicated than suggested by the simple concepts of early studies. The overall results illustrate where in the cycles well‐defined, long‐lived large scale structures can be expected, and the advantages of synoptic displays of 1 AU solar wind parameters for anticipating timings of recurring features.